The lean enterprise : how corporations can innovate like startups - Owens, Trevor; Fernandez, Obie (Wiley, 2014)
"Presents a groundbreaking design for revolutionizing larger organizations, one that draws on the ingenious tenets and practices espoused by the startup community. The guidelines in this book will help companies shake the lethargy, bureaucracy, and power struggles that plague large organizations and hold them back from true innovation. At the heart of this resource is a comprehensive, practical approach based on methods, timetables, compensation, financial investment, and case studies that reveal the startup mentality. Respected thought leaders in lean startup methodologies, the authors cover successful enterprise development, development innovation labs, corporate venture arms, and acquisition and integration of startups."- Resumé vydavatel
Obsahuje index.
Keywords: management inovací; podnikový management; produktový management; innovation management; industrial management; product management; štíhlá výroba; monografie; elektronické knihy; monographs; electronic books